INTEGRATING LANGUAGE SKILLS IN BILINGUAL EDUCATION - Abdulhamidova, Sarvinoz (FILOLOGIYA UFQLARI JURNALI, 2025)
Bilingual education plays a crucial role in shaping the future of linguistic and cognitive development, particularly in countries where multiple languages coexist. The integration of language skills in bilingual education is a dynamic and evolving field, influenced by a wide range of factors including cultural, social, and educational contexts. This coursework explores the intricacies of bilingual education with a particular focus on integrating language skills effectively within the curriculum, as well as how it can benefit learners in a multicultural society, such as Uzbekistan. The theme of integrating language skills is both timely and vital, given the growing demand for bilingualism in globalized societies, where the ability to communicate in multiple languages is an essential skill for personal and professional development.